2021
DOI: 10.1097/aln.0000000000003868
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Neurons in the Dorsal–Intermediate Lateral Septum Regulate Sleep–Wakefulness and Anesthesia in Mice

Abstract: Background The γ-aminobutyric acid–mediated (GABAergic) inhibitory system in the brain is critical for regulation of sleep–wake and general anesthesia. The lateral septum contains mainly GABAergic neurons, being cytoarchitectonically divided into the dorsal, intermediate, and ventral parts. This study hypothesized that GABAergic neurons of the lateral septum participate in the control of wakefulness and promote recovery from anesthesia. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The lateral septum contains GABAergic neurons that project to multiple wakefulnesspromoting subregions. The calcium activity of the dorsal-intermediate lateral septal GABAergic neuron changes in both the processes of induction and emergence, similar to the trend observed in the sleep-wake cycle [55]. Collectively, these in vivo calcium imaging findings suggest that multiple brain nuclei and neural circuits known to regulate the sleep-wake cycle play a similar role in general anesthesia (Table 1).…”
Section: In Vivo Calcium Imagingsupporting
confidence: 70%
See 1 more Smart Citation
“…The lateral septum contains GABAergic neurons that project to multiple wakefulnesspromoting subregions. The calcium activity of the dorsal-intermediate lateral septal GABAergic neuron changes in both the processes of induction and emergence, similar to the trend observed in the sleep-wake cycle [55]. Collectively, these in vivo calcium imaging findings suggest that multiple brain nuclei and neural circuits known to regulate the sleep-wake cycle play a similar role in general anesthesia (Table 1).…”
Section: In Vivo Calcium Imagingsupporting
confidence: 70%
“…Chemogenetic activation of these neurons reliably produces slow-wave sleep and facilitates general anesthesia, and chemogenetic inhibition shortens the general anesthesia time and disrupts natural sleep [ 9 ]. Recent studies have found that chemogenetic activation of GABAergic neurons in other brain regions, such as the VTA [ 79 ] and RMTg [ 80 ], promotes an anesthesia state as well, whereas chemogenetic activation of dorsal–intermediate lateral septum GABAergic neurons contributes to anesthesia emergence [ 55 ]. The fact that sleep-promoting GABAergic neurons in the aforementioned regions similarly contribute to anesthetic-state transitions further supports a common regulatory mechanism between the states of sleep and general anesthesia ( Table 1 ).…”
Section: Chemogeneticsmentioning
confidence: 99%
“…The lateral septum (LS) is implicated as a hub that regulates affective behaviors, such as reward, feeding, anxiety, fear, sociability, and memory [6][7][8]. It is well known that LS neurons are predominantly GABAergic, with only a small population of glutamatergic cells in the most ventral region [9].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral hypothalamic area (LH) is a vital controller of arousal, feeding, and metabolism, integrating sensory information about the world and the body [8,16]. The LH had been identified as a brain region responsive to pain stimuli and chronic pain-induced maladaptive anxiety that is capable of controlling pain-related behavioral responses by feeding [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The paraventricular hypothalamic nucleus (PVH), located in the ventral diencephalon adjacent to the third ventricle, has dense mutual projections with structures that modulate sleep–wake behaviors, including the locus coeruleus (LC), 6,7 the parabrachial nucleus (PB), 8,9 the ventrolateral preoptic nucleus (VLPO), PVT, the lateral septum (LS) 10,11 . Previous studies have confirmed that the LC, VLPO, PVT, and LS regulated sleep–wakefulness and anesthesia 3,4,6,9 . The PVH is mostly composed of neuroendocrine neurons, containing corticotropin‐releasing hormone, 12 oxytocin 11 and prodynorphin, 13 in which all the neurons predominantly co‐expressed the mRNA of vesicular glutamate transporter 2 (vglut 2).…”
Section: Introductionmentioning
confidence: 99%